(untitled) (Journal of Academic Research, 2021)
Samples of Megalaspis cordyla (Al-Sabari) and Scomber japonicus (Al-Taboub) were collected from fishermen from the coasts of Mukalla City (Hadhramout Governorate) 2020. Transferred to the Biology Laboratory, Faculty of Science/ Hadhramout University. 30 samples of varying lengths and sizes were used for anatomical and histological examination of both types. The morphometric study included measurements of the external lengths of the fish represented in the total length and spinal length. The study also included measuring the total length and weight of the spleen. These measurements are recorded in graphic form and explained, analyzed and discussed. Haematoxylin and Eosin stains were used to detect the components of spleen tissue using light microscopy. Microscopic examination of the cross-sectional histological sections of the spleen showed that it consisted of a capsule containing many red pulps in addition to the presence of large black melanocytes in M. cordyla fish and small splenic arterioles in S. japonicus fish.